Impact of postoperative changes in sarcopenic factors on outcomes after hepatectomy for hepatocellular carcinoma. (3rd December 2015) - Kobayashi, Atsushi; Kaido, Toshimi; Hamaguchi, Yuhei; Okumura, Shinya; Taura, Kojiro; Hatano, Etsuro; Okajima, Hideaki; Uemoto, Shinji
Abstract: Background: We have reported that preoperative low skeletal muscle quality was an independent risk factor for poor outcomes after hepatectomy for hepatocellular carcinoma (HCC). However, postoperative changes of quality as well as quantity of skeletal muscle after hepatectomy for HCC and their impact on postoperative outcomes have not been fully investigated. Methods: We retrospectively analyzed 241 patients undergoing primary hepatectomy for HCC between January 2007 and September 2012. The quality and quantity of skeletal muscle were evaluated by intramuscular adipose tissue content (IMAC) and the psoas muscle mass index (PMI) using computed tomography imaging at the umbilical level, respectively. We evaluated postoperative changes in IMAC and PMI in patients according to preoperative sarcopenia, sex, and surgical procedure. We also investigated the impact of ΔIMAC and ΔPMI on HCC recurrence in patients with preoperative normal IMAC. Results: On multivariate analysis, indocyanine green retention test at 15 min ≥ 15% (odds ratio [OR] = 3.156; P = 0.041) and high ΔIMAC at 6 months after hepatectomy (OR = 3.713; P = 0.024) were the risk factors for HCC recurrence in patients with preoperative normal IMAC. Conclusion: Postoperative depletion of skeletal muscle quality is closely involved with HCC recurrence after hepatectomy for HCC. Abstract : Highlight This study by Kobayashi and colleagues is the first to investigate the impact of postoperative changes in quality and quantity of skeletal muscle on outcomes after hepatectomy for hepatocellular carcinoma. Reduced postoperative muscle quality was an independent risk factor for recurrence, suggesting the importance of postoperative exercise and nutritional therapy